Uma visão semiótica da experiência do usuário - Oliveira, Amanda Porto de (2016)
The purpose of this study takes as a goal the semiotics investigation of the effects of perception and aesthetics in the human experience through technology. With the design’s evolution related to search of simple as an important aspect, the user experience starts to be seen as an essential methodology to products and systems concept. UX wraps perceptions and reactions resulting of the technology planned. Charles Sanders Peirce’s vision about the forms of perception and senses is the study’s base, which recognizes in user experience the regular’s way of meanings in semiosis unlimited process. The experience’s chains also are identified from the moment that perception acts on us - and against us - up to the recognition elements that compose the quality of the admirable inside the aesthetic experience